Creative Economy in the Traditional and Modern Islamic Boarding Schools in Serang Banten Province - Fahmi Raudhatul Ulum; Purnama Rika Perdana (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2021)
Islamic boarding school is one type of Islamic education in Indonesia that is traditional and has unique characteristics, both the education system, learning system, and its goals and functions. This paper examines the creative economy model in Islamic boarding schools in Serang, Banten Province. This research uses a qualitative approach, while the design of this research uses a case study design, which seeks to describe a specific setting, object, or event in detail. Data were collected from 16 Salafi and modern Islamic boarding schools, while the location of this research is in modern and Salafi Islamic boarding schools around Serang. Data collecting is done through the questionnaire filled by the students of the Islamic boarding school. The findings of this study are: First, the entrepreneurial values ​​internalized by Islamic boarding schools in Serang are the values ​​of worship-based entrepreneurship, where all economic activities carried out are intended to worship Allah SWT. Second, the creative economic process was carried out with a strategy of being trained to manage the existing economic institutions in the Islamic boarding school under the supervision and guidance of the Kiai and the board of the Islamic boarding school.